Networking IP Restriction filtering and network address - Bein, Adrian Sean; Williams, Alexander (Pandawan Sejahtera Indonesia, 2020)
Permissions setting on a computer is necessary. This is an effort that is not easy to change the system configuration or settings changed by the user. With a network of computers, of course, permissions settings do not need to be done one by one manually. Because in a computer network course there are many collections of computers connected together. Permissions setting so that the system can use the client-server applications that access restrictions can be done effectively. As the implementation of client-server applications can be created using Visual Basic 6.0. This language has been able to access the socket on the Windows operating system, named Winsock API that supports TCP / IP. This protocol is widely used because of the reliability of client-server application programming. The application is divided into two main applications, namely the client and server program name with the name of the Receiver Sender program. Receiver function receives instructions restriction of access rights Sender and sends reports to the Sender process execution. While Sender functions to send instructions restrictions permissions via the Registry to the Receiver. And after the test, the application can block important features available in the Windows operating system. So it is expected that these applications can help in permissions setting on a computer network.